Respostas
respondido por:
0
a1 = - 3
r = 2
an = a1 + (n - 1).r
a2 = a1 + (2 - 1)r
a2 = a1 + r
a2 = - 3 + 2
a2 = - 1
a3 = a1 + 2r = - 3 + 2.2 = - 3 + 4 = 1
a4 = a1 + 3r = - 3 + 3.2 = - 3 + 6 = 3
Resp.:
PA: (- 3, - 1, 1 , 3)
r = 2
an = a1 + (n - 1).r
a2 = a1 + (2 - 1)r
a2 = a1 + r
a2 = - 3 + 2
a2 = - 1
a3 = a1 + 2r = - 3 + 2.2 = - 3 + 4 = 1
a4 = a1 + 3r = - 3 + 3.2 = - 3 + 6 = 3
Resp.:
PA: (- 3, - 1, 1 , 3)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás